Datum Geodetik Batas Maritim Indonesia â Singapura: Status dan Permasalahannya - Hasanuddin Z. Abidin; K. J. Villanueva; Sobar Sutisna; T. Padmasari (Journal of Mathematical and Fundamental Sciences, 2005)
Maritime boundary between Indonesia and Singapore in the strait of Singapore has been defined by the territorial sea boundary treaty of 1973.In this treaty, geodetic datum of the geographic coordinates of six boundary points between Indonesia and Singapore are not explicitly stated. This paper investigates the possible datum for these coordinates, namely KERTAU48, KERTAU68, GENUK and SOUTH ASIA, and its impacts on the coordinates and location of boundary points. Related aspects are also discussed. Paper is sum up with some conclusions and recommendations.